Gender differentials in labour market participation of rural households in non-farm activities in oyo state, nigeria (2018)
Gender inequities in labour market opportunities is a particular concern since earnings from labour supplies are the most important source of income for the poor in the rural economies of developing countries. This study examined gender differentials in labour market participation of rural households in non-farm activities in Oyo state, Nigeria. A multistage random sampling technique was employed in selecting 120 rural households. Descriptive Statistics, Double- Hurdle regression model and Multinomial Logit regression models were the analytical tools employed. The mean farm size was relatively small as more than three-quarters of both male and female headed households respectively cultivated less than 1 hectare. Regression results indicated that male and female headed households participated and allocated more time to non-farm activities as their age and household size increased while farm size and remittances had negative effects. The decision on whether a household would hire or supply labour was largely influenced by the age of the household head, farm size, farming experience, household size and being a member of a cooperative group. However, female headed households’ participation was constrained mainly by inaccessibility to town as a result of the long distance between the homestead and the nearest town. The study recommends the establishment of small and medium enterprises in the rural areas to encourage the participation of both male and female headed households in non-farm income generating activities to cushion declining farm incomes